Pengaruh CR, ROA dan DER terhadap Harga Saham : (Pada Perusahaan Food and Beverages Terdaftar di BEI 2019-2022) - Muh Lutfy Mahendra Wijaya; Johanis Souisa; Ade Wicak Wibisono; Afreyzal Athillah Izzulhaq; Abdul Syafiq (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to examine the influence of the Current Ratio, Return on Assets, and Debt to Equity Ratio on shares in consumer goods companies in 2019-2022. The population in this study are manufacturing companies in the consumer goods industry sector, food and beverage subsector, which are listed on the Indonesia Stock Exchange for the 2019-2022 period. The total population in that period was 23 companies. The type of data used in this research is secondary data, namely data obtained from written sources related to research. The analytical method of this research is quantitative data which will then be processed using SPSS 23. The results of this research prove that the Current Ratio has an insignificant effect on stock prices, Return of Assets has an insignificant effect on stock prices, Debt to Equity Ratio has an insignificant effect on prices. share.